Soil fertility status under mixed pastures in irrigated Tsitsikamma dairy farms: case studies - Loke, P. F.; Kotzé, E.; Du Preez, C. C. (Springer, 2024)
Animal manures are increasingly receiving renewed interest as an alternative to synthetic fertilizers. While they may improve ecosystem functions, there is limited information on short-term effects of organic amendments on soil reaction and nutrient dynamics in irrigated mixed dairy pastures, especially in the context of the Tsitsikamma region, South Africa. This study examined the soil fertility status of minimum tilled 6-year-old pasture-mixed dairy farms (F1, F2, F3, F4 and F5) in the Upper (UT) and Lower (LT) Tsitsikamma regions treated with different rates of NPK (nitrogen, phosphorus, potassium) fertilizer alone or in combination with poultry manure (PM) and/or dairy effluent (DE). Soil samples were collected at 0–15, 15–30, 30–45 and 45–60 cm depth intervals and analysed for soil pH, P, K, Ca and Mg. Results of this study revealed variable trends on soil pH and nutrient changes between farms, suggesting an influence of some inherent soil properties in addition to the 6-year applied management practices. When averaged over sampled farms, surface placement of soil amendments and limited soil disturbance resulted in surface stratification of soil pH, P, K, Ca and Mg. On the other hand, integration of organic and inorganic fertilizers induced significant changes in nutrient contents and stocks to a depth of 60 cm, especially in the LT region. A combination of NPK fertilizer, PM and/or DE applied in pasture mixtures generally showed potential to improve soil fertility in both regions. As such, adoption of this combination by farmers could cut down reliance on expensive synthetic fertilizers and costs of dairy production. However, studies are still necessary in this region to validate the observed results.
Keywords: Animal manure; Mixed dairy pastures; Plant nutrients; Soil fertility; South Africa